2011
DOI: 10.1007/s10562-011-0631-1
|View full text |Cite
|
Sign up to set email alerts
|

Cyclization of Pseudoionone into α-Ionone Over Heteropolyacid Supported on Mesoporous Silica SBA-15

Abstract: Cyclization of pseudoionone into a-ionone was performed over the series heteropolyacid supported on SBA-15 in liquid-phase at 363 and 373 K using a batch reactor. It has been demonstrated that the liquid-phase synthesis of a-ionone by pseudoionone cyclization can be efficiently achieved on heteropolyacid/SBA-15 materials. The high catalytic performance of PW 12 /SBA-15 materials is due to their strong Brønsted acidity, high dispersion of active phase and also to absence of steric constraints for pseudoionone c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 18 publications
1
0
0
Order By: Relevance
“…Those results showed that at PS isoconversion the contribution of α-ionone increases from 35 to 45.2% at the expense of γ-ionone as the reaction temperature increases from 343 to 383 K. Thus, at high reaction temperatures α-ionone is the main product on HPAS-59. A similar result was obtained by Rachwalik et al [17] using HPA/SiO 2 and HPA/SBA-15 catalysts. The analysis of the dependence of β isomer concentration with reaction temperature showed that β-ionone contribution remains almost constant at increasing temperatures taking values around 20%; that result confirmed that β-ionone is a primary and terminal product on HPA-based samples and that isomer interconversion is limited to isomerization of the γ isomer toward α-ionone.…”
Section: Effect Of the Reaction Temperature In Hpas-x Catalystssupporting
confidence: 88%
“…Those results showed that at PS isoconversion the contribution of α-ionone increases from 35 to 45.2% at the expense of γ-ionone as the reaction temperature increases from 343 to 383 K. Thus, at high reaction temperatures α-ionone is the main product on HPAS-59. A similar result was obtained by Rachwalik et al [17] using HPA/SiO 2 and HPA/SBA-15 catalysts. The analysis of the dependence of β isomer concentration with reaction temperature showed that β-ionone contribution remains almost constant at increasing temperatures taking values around 20%; that result confirmed that β-ionone is a primary and terminal product on HPA-based samples and that isomer interconversion is limited to isomerization of the γ isomer toward α-ionone.…”
Section: Effect Of the Reaction Temperature In Hpas-x Catalystssupporting
confidence: 88%